Strengthening the figure skater: Considerations for injury prevention and performance - Mohney, G.; Miller, M. G.; Hanson, N. (Strength and Conditioning Journal, 2017)
Athletes who participate in various figure skating disciplines could benefit from specific strengthening exercises targeting the trunk, hip, and lower extremity to prevent injury and enhance performance. Particular attention should be placed on strengthening the transverse abdominis, multifidus, and gluteal muscles followed by balance and power training. The exercise programs presented should also increase postural control and reduce the incidence of hip-related injury in skaters. In addition, these exercises can be completed during the entire training year, with reduced intensity and volume of work lower during specific competition periods.